2021
DOI: 10.1111/apa.16143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timing of PERT on gastrointestinal symptoms in Danish children and adolescents with CF

Abstract: Aim: Gastrointestinal (GI) symptoms are often reported by CF patients. Despite a proven relation to exocrine pancreatic insufficiency (PI), it remains unclear whether GI symptoms are related to the timing of pancreatic enzyme replacement therapy (PERT). Whereas most international recommendations suggest administration of PERT at the beginning of meals, it has not been studied whether such a proceeding is associated with lower burden of symptoms. Methods: Thirty CF patients aged 0-17 years of age with PI were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…The CFAbd-Score has been translated into nine languages including Italian, Spanish, Portuguese, French, Dutch, Flemish and Danish, and therefore, it has been included in an international European multicentre trial (MyCyFapp) in order to assess abdominal symptoms during a project for optimization of PERT supplementation (Boon et al, 2020). Also a Danish group from the Copenhagen CF Centre assessed optimal timing of PERT, with inclusion of the CFAbd-Score (Raun et al, 2022). Besides these international projects, our PROM is presently implemented in a series of academic and industry studies.…”
Section: Validation Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…The CFAbd-Score has been translated into nine languages including Italian, Spanish, Portuguese, French, Dutch, Flemish and Danish, and therefore, it has been included in an international European multicentre trial (MyCyFapp) in order to assess abdominal symptoms during a project for optimization of PERT supplementation (Boon et al, 2020). Also a Danish group from the Copenhagen CF Centre assessed optimal timing of PERT, with inclusion of the CFAbd-Score (Raun et al, 2022). Besides these international projects, our PROM is presently implemented in a series of academic and industry studies.…”
Section: Validation Of Thementioning
confidence: 99%
“…Elaborated in four published steps, the first version of this CF-specific questionnaire (initially named JenAbd-Score, and from then CFAbd-Score) aimed to assess and quantify abdominal involvement in pwCF, and its development included patients, proxies and health care specialists, as recommended by FDA guidelines (Tabori et al, 2017a;Tabori et al, 2017b;Jaudszus et al, 2019). At present, the CFAbd-Score is available in nine languages and implemented in many international studies (Boon et al, 2020;Jaudszus et al, 2021;Ng et al, 2021;Raun et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the PROM had been named JenAbd-Score (Tabori et al, 2017a), and after condensing it from a 5-sided questionnaire to a one-sided PROM, which comprises 28 symptoms grouped in five domains, it was renamed "CFAbd-Score" (Tabori et al, 2017b;Jaudszus et al, 2019;Mainz et al, 2023;Jaudszus et al, 2022;Mainz et al, 2022;Caley et al, 2023b). Presently, it is available in eleven languages and implemented in more than 25 studies around the world (Boon et al, 2020;Mainz et al, 2023;Ng et al, 2021;Mainz et al, 2022;Raun et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We recently studied the PERT intake in our paediatric CF population and found that GI symptoms were common and did not improve by changing the timing of the PERT intake from before to after meals [ 17 ]. In the present study, we aimed to describe use of PERT and GI symptoms among adults with CF and to assess the associations between PERT dose and the demographic and clinical characteristics of pwCF.…”
Section: Introductionmentioning
confidence: 99%